Implikasi Teologis Baptisan Air pada Keselamatan - Harefa, Otieli (PASCA : Jurnal Teologi dan Pendidikan Agama Kristen, 2020)
This paper is a theological analysis of water baptism and its relation to salvation. The church requires this sacrament as evidence of new birth or repentance. Regardless of the method of its implementation, the issue concerning this sacrament is about its theological significance which has led to many interpretations within the church, especially in relation to the concept of salvation. This article discusses the concept of water baptism from its Hebrew roots to its application in the New Testament and Paul’s letters. This study uses a descriptive qualitative approach, in which the data are obtained in the form of explanations of concepts or texts and not numbers. The analysis concludes that water baptism leads one to accept the promise of God, unity with Christ, and genuine conversion to Christ, which is essentially an aspect of the salvation of a believer or believer